Study of Receptor Status in Carcinoma Breast Patient - Ahmed, Shakera; Azad, Khondker AK (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Estimation of Estrogen Receptor (ER) Progesterone Receptor (PR) and Human Epidermal Growth Factor Receptor 2 (HER2) is mandatory for choosing treatment options and prognosis of breast cancer patients. This estimation can be done by Immunohistochemistry (IHC) and Fluoroscence In Situ Hybridization (FISH) test. As the tests are expensive many of our patients can’t afford to do it. But if we practice doing the test routinely the cost will be reduced and our patients will be benefited. So we underwent a primitive study on receptor status in breast cancer patients. Our goal was to encourage the surgeons to advice receptor status routinely and treat the patients accordingly as patients prognosis will be much more better if they are treated according to their receptor status. Methods: This was a retrospective observational study of 74 breast cancer patients in a private clinic. In this study we have shown their receptor status by IHC and the data were analyzed. Results: Among the 74 patients 32 were ER +ve PR +ve, 11 were ER +ve PR -ve, 02 were ER –ve PR +ve, 29 were ER -ve PR -ve. ER &/or PR positive patients will be more responsive to hormone therapy. 28 patients were HER2 +ve, 34 patients were HER2 –ve and 9 were equivocal. HER2 positive patients will be benefited from targeted therapy. Among the patients 11 were triple negative that means they have worst prognosis. Conclusion: As knowing the receptor status in breast cancer help us as a predictive, prognostic and therapeutic indicator, we must advice it routinely and take steps to make it cheaper and easily available. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 48-50